The polynomial function

Algebra Level 4

Given that f ( x ) f(x) is a polynomial satisfying f ( x ) f ( y ) = f ( x ) + f ( y ) + f ( x y ) 2 f(x)f(y)=f(x)+f(y)+f(xy)-2 and f ( 2 ) = 5 f(2)=5 , find f ( 3 ) f(3) .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

It is given that: f ( x ) f ( y ) = f ( x ) + f ( y ) + f ( x y ) 2 \space f(x)f(y) = f(x) + f(y) + f(xy) - 2 , where f ( x ) = k = 0 n a k x k \space f(x) = \displaystyle \sum_{k=0}^n a_kx^k .

Therefore, we have f ( 0 ) f ( 2 ) = f ( 0 ) + f ( 2 ) + f ( 0 ) 2 Since f ( 2 ) = 5 5 f ( 0 ) = f ( 0 ) + 5 + f ( 0 ) 2 f ( 0 ) = 1 f ( x ) = k = 1 n a k x k + 1 \begin{aligned} \text{Therefore, we have } \space f(0)\color{#3D99F6}{f(2)} & = f(0) + \color{#3D99F6}{f(2)} + f(0) - 2 \quad \quad \small \color{#3D99F6}{\text{Since } f(2) = 5} \\ \color{#3D99F6}{5}f(0) & = f(0) + \color{#3D99F6}{5} + f(0) - 2 \\ \Rightarrow f(0) & = 1 \\ \Rightarrow f(x) & = \sum_{k=1}^n a_kx^k + 1 \end{aligned}

And, we have f ( 1 ) f ( 2 ) = f ( 1 ) + f ( 2 ) + f ( 2 ) 2 5 f ( 1 ) = f ( 1 ) + 2 ( 5 ) 2 f ( 1 ) = 2 f ( x ) f ( 1 x ) = f ( x ) + f ( 1 x ) + f ( 1 ) 2 = f ( x ) + f ( 1 x ) + 2 2 f ( x ) f ( 1 x ) = f ( x ) + f ( 1 x ) \begin{aligned} \text{And, we have } \space f(1)\color{#3D99F6}{f(2)} & = f(1) + \color{#3D99F6}{f(2)} + \color{#3D99F6}{f(2)} - 2 \\ \color{#3D99F6}{5}f(1) & = f(1) +2(\color{#3D99F6}{5}) - 2 \\ \Rightarrow f(1) & = 2 \\ \Rightarrow f(x)f\left(\frac{1}{x}\right) & = f(x) + f\left(\frac{1}{x}\right) + f(1) - 2 \\ & = f(x) + f\left(\frac{1}{x}\right) + 2 - 2 \\ \Rightarrow f(x)f\left(\frac{1}{x}\right) & = f(x) + f\left(\frac{1}{x}\right) \end{aligned}

Therefore, the polynomial must be of the form f ( x ) = ( x n + 1 ) \space f(x) = (x^n + 1) , so that:

f ( x ) f ( 1 x ) = ( x n + 1 ) ( 1 x n + 1 ) = 1 + x n + 1 x n + 1 = f ( x ) + f ( 1 x ) \begin{aligned} f(x)f\left(\frac{1}{x}\right) & = (x^n + 1) \left(\frac{1}{x^n} +1\right) \\ & = 1 + x^n + \frac{1}{x^n} + 1 \\ & = f(x) + f\left(\frac{1}{x}\right) \end{aligned}

Since f ( 2 ) = 5 f(2) = 5 , f ( x ) = x 2 + 1 f ( 3 ) = 3 2 + 1 = 10 \Rightarrow f(x) = x^2 + 1 \quad \Rightarrow f(3) = 3^2+1 = \boxed{10}

Tom Engelsman
Oct 17, 2015

If f(x) is a polynomial, then it is differentiable over all real x. Differentiating the above functional equation with respect to x and y each gives:

f ( x ) f ( y ) = f ( x ) + y f ( x y ) (i) f'(x)f(y) = f '(x) + yf'(xy) \tag{i}

f ( x ) f ( y ) = f ( y ) + x f ( x y ) (ii) f(x)f'(y) = f'(y) + xf'(xy) \tag{ii}

and equating (i) with (ii) yields:

x f ( x ) f ( x ) 1 = y f ( y ) f ( y ) 1 = A (real constant) (iii) \frac{xf'(x)}{f(x)-1} = \frac{yf'(y)}{f(y)-1} = A \ \text{(real constant)} \tag{iii}

and integrating (iii) with respect to x x gives:

ln [ f ( x ) 1 ] = A ln x + B \ln[f(x)-1] = A\ln x + B

or

f ( x ) = e B x A + 1 (iv) f(x) = e^Bx^A + 1 \tag{iv}

Plugging in the boundary condition f(2) = 5 will produce

4 = e B × 2 A 2 2 = e B × 2 A 4 = e^B \times 2^A \Rightarrow 2^2 = e^B \times 2^A

which holds only for A = 2 , B = 0 A = 2, B = 0 . Thus, the sought polynomial is f ( x ) = x 2 + 1 f(x) = x^2 + 1 with f ( 3 ) = 10 f(3) = \boxed{10} .

Hey Tom, I enjoyed your solution so I've LaTeXified your solution, such that it's easier to digest! You may move your mouse arrow over LaTeX expressions to view them in LaTeX form, and there are multiple sources online to help you learn LaTeX. Happy solving!

Jake Lai - 5 years, 7 months ago

Log in to reply

Thanks, Jake! I'm trying to teach myself LaTeX on the side.......definitely does help make my derivatives more legible :)

tom engelsman - 5 years, 7 months ago

A Nice question!!:):)

I t s g i v e n t h a t f ( x ) . f ( y ) = f ( x ) + f ( y ) + f ( x y ) 2 A l s o , f ( 2 ) = 5. e q . 1 S u b s t i t u t e x = 2 i n f i r s t e q u a t i o n f ( 2 ) . f ( y ) = f ( 2 ) + f ( y ) + f ( 2 y ) 2 5 f ( y ) = 5 + f ( y ) + f ( 2 y ) 2 4 f ( y ) = 3 + f ( 2 y ) f ( 2 y ) = 4 f ( y ) 3 It's\quad given\quad that\quad f\left( x \right) .f\left( y \right) =f\left( x \right) +f\left( y \right) +f\left( xy \right) -2\\ Also,\quad f\left( 2 \right) =5.\quad \quad \quad \quad \longrightarrow eq.1\\ Substitute\quad x=2\quad in\quad first\quad equation\\ f\left( 2 \right) .f\left( y \right) =f\left( 2 \right) +f\left( y \right) +f\left( 2y \right) -2\\ 5f\left( y \right) =5+f\left( y \right) +f\left( 2y \right) -2\\ 4f\left( y \right) =3+f\left( 2y \right) \\ f\left( 2y \right) =4f\left( y \right) -3

N o w , p u t y = 1 : f ( 2 y ) = 4 f ( y ) 3 f ( 2 ) = 4 f ( 1 ) 3 5 + 3 = 4 f ( 1 ) f ( 1 ) = 2 e q . 2 Now,\quad put\quad y=1:\\ f\left( 2y \right)=4f\left( y \right)-3\\ f\left( 2 \right)=4f\left( 1 \right)-3\\ 5+3=4f\left( 1 \right)\\ f\left( 1 \right)=2\quad \quad \quad \quad \quad \longrightarrow eq.2

S i m i l a r l y , p u t y = 2 f ( 2 y ) = 4 f ( y ) 3 f ( 4 ) = 4 ( f ( 2 ) ) 3 f ( 4 ) = 20 3 f ( 4 ) = 17 e q . 3 Similarly,\quad put\quad y=2\\ f\left( 2y \right) =4f\left( y \right) -3\\ f\left( 4 \right) =4(f\left( 2 \right) )-3\\ f\left( 4 \right) =20-3\\ f\left( 4 \right) =17\quad \quad \quad \quad \quad \longrightarrow eq.3

F r o m e q . 1 , e q . 2 , a n d e q . 3 w e c a n d e d u c e t h a t f ( x ) = x 2 + 1 T h e r e f o r e , f ( 3 ) = 3 2 + 1 f ( 3 ) = 10 From\quad eq.1,\quad eq.2,\quad and\quad eq.3\\ we\quad can\quad deduce\quad that\quad \\ f\left( x \right)={ x }^{ 2 }+1\\ Therefore,\quad f\left( 3 \right)={ 3 }^{ 2 }+1\\ \Rightarrow f\left( 3 \right)=10

Cheers!!:):)

How do you know that the polynomial must be a quadratic function? For example, we could have f ( x ) = A ( x 1 ) ( x 2 ) ( x 4 ) + x 2 + 1 f(x) = A ( x-1)(x-2)(x-4) + x^2 + 1 .

If you are not given the value of f ( 2 ) f(2) , what is the general solution look like?

Calvin Lin Staff - 6 years, 10 months ago
Brian Moehring
Aug 7, 2018

Note that f ( x ) f ( y ) = f ( x ) + f ( y ) + f ( x y ) 2 ( f ( x ) 1 ) ( f ( y ) 1 ) = f ( x y ) 1 f ( x n ) 1 = ( f ( x ) 1 ) n , n 1 f ( 2 n ) = 1 + ( f ( 2 ) 1 ) n = 1 + 4 n = 1 + ( 2 n ) 2 , n 1 \begin{aligned} f(x)f(y) &= f(x)+f(y)+f(xy) - 2 \iff (f(x)-1)(f(y)-1) = f(xy)-1 \\ &\implies f(x^n)-1 = \left(f(x)-1\right)^n,\quad \forall n \geq 1 \\ &\implies f(2^n) = 1 + \left(f(2)-1\right)^n = 1 + 4^n = 1 + \left(2^n\right)^2, \quad \forall n \geq 1 \end{aligned}

Since f ( x ) = 1 + x 2 f(x) = 1 + x^2 for the infinitely many values x = 2 n x=2^n for positive integers n n and f f is a polynomial, it follows that f ( x ) = 1 + x 2 f(x) = 1 + x^2 for all x x .

In particular, f ( 3 ) = 1 + 3 2 = 10 f(3) = 1 + 3^2 = \boxed{10}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...